Bouncing models - Pinto Neto, Nelson (Cadernos de Astronomia, 2023)
Recent cosmological and astrophysical observations indicate that the Universe is expanding, with a very hot phase in the past, which for many indicates the beginning of the Universe. In this article, I intend to motivate and describe cosmological models where the Universe did not have a beginning and will not have an end, containing a long contraction phase followed by a bounce that launches it into the currently observed expansion phase. That is why they are called Bouncing Models. In the context where there are infinite contraction and expansion phases, with bounces between them, they are also called Cyclic Models. This set of models will be theoretically motivated, and confronted with the most recent cosmological observations. It will also be compared with models where the Universe had a beginning followed by an inflationary phase, which will be explained in other articles in this issue of Cadernos de Astronomia.
Keywords: cosmology; bouncing models; extensions of general relativity; cosmological observations